Solve for z 0.2(z-3)-z=0.2

Math
0.2(z-3)-z=0.2
Simplify 0.2(z-3)-z.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
0.2z+0.2⋅-3-z=0.2
Multiply 0.2 by -3.
0.2z-0.6-z=0.2
0.2z-0.6-z=0.2
Subtract z from 0.2z.
-0.8z-0.6=0.2
-0.8z-0.6=0.2
Move all terms not containing z to the right side of the equation.
Tap for more steps…
Add 0.6 to both sides of the equation.
-0.8z=0.2+0.6
Add 0.2 and 0.6.
-0.8z=0.8
-0.8z=0.8
Divide each term by -0.8 and simplify.
Tap for more steps…
Divide each term in -0.8z=0.8 by -0.8.
-0.8z-0.8=0.8-0.8
Cancel the common factor of -0.8.
z=0.8-0.8
Divide 0.8 by -0.8.
z=-1
z=-1
Solve for z 0.2(z-3)-z=0.2

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top